PENGARUH DEEP BREATHING EXERCISE PADA KASUS PNEUMONIA TERHADAP PENURUNAN SESAK DENGAN PARAMETER DYSPNEA SEVERITY SCALE DI RS PARU DR. M. GOENAWAN PARTOWIDIGDO TAHUN 2021 - Mohammad Ali; Erna Sariana; Erna Satwika Retno Pamungkas (Jurnal Fisioterapi dan Kesehatan Indonesia, 2022)
Background: Pneumonia is an inflammatory condition of the lung parenchyma of the alveoli, bronchi, and bronchioles. Pneumonia is most often caused by the bacterium Streptococcus pneumoniae, but viruses can also cause pneumonia. Dr. M. Goenawan P Lung Hospital from 2018 to 2020 a total of 5657 patients, with details of Outpatient 1628 patients and Inpatient 4029 patients. Dyspnea is a common symptom of both cardiopulmonary and neuromuscular disease. The Dyspnea Severerity Scale is to develop and validate a simple scoring system for evaluating the severity of dyspnea in emergency care, based on objectively measured parameters. Objective: To know the effect of deep breathing exercise in pneumonia cases to reduce shortness of breath with the Dyspnea Severity Scale parameter at RS Paru dr.M.Goenawan P in 2021. Results: The correlation value in the Paired Sample Test obtained is 0.928, which is close to the value of 1, so the research data has a strong correlation. P Value 0.000 <0.05, it means that there is a significant difference between before and after the intervention. So it can be concluded that There is a significant effect of giving Deep Breathing Exercise in cases of pneumonia on reducing shortness of breath with the Dyspnea Severity Scale parameter. Conclusion: Intervention in the form of Deep Breathing Exercise, measured using the Dyspnea Severity Scale parameter, can reduce shortness of breath in cases of pneumonia.